Layer‐by‐Layer Motif Architectures: Programmed Electrochemical Syntheses of Multilayer Mesoporous Metallic Films with Uniformly Sized Pores. Issue 27 (5th June 2017) - Jiang, Bo; Li, Cuiling; Qian, Huayu; Hossain, Md. Shahriar A.; Malgras, Victor; Yamauchi, Yusuke
Abstract: Although multilayer films have been extensively reported, most compositions have been limited to non‐catalytically active materials (e.g. polymers, proteins, lipids, or nucleic acids). Herein, we report the preparation of binder‐free multilayer metallic mesoporous films with sufficient accessibility for high electrocatalytic activity by using a programmed electrochemical strategy. By precisely tuning the deposition potential and duration, multilayer mesoporous architectures consisting of alternating mesoporous Pd layers and mesoporous PdPt layers with controlled layer thicknesses can be synthesized within a single electrolyte, containing polymeric micelles as soft templates. This novel architecture, combining the advantages of bimetallic alloys, multilayer architectures, and mesoporous structures, exhibits high electrocatalytic activity for both the methanol oxidation reaction (MOR) and the ethanol oxidation reaction (EOR). Abstract : Filming in progress : Mesoporous films of Pd, Pt, and PdPt were produced by electrodeposition with good control over their thicknesses. The multilayer, bimetallic PdPt film in particular showed high electroactivity toward the oxidation of both ethanol and methanol.